Construction of Liposomes Mimicking Cell Membrane Structure through Frame‐Guided Assembly. (9th June 2020) - Wang, Chao; Piao, Jiafang; Li, Yujie; Tian, Xiancheng; Dong, Yuanchen; Liu, Dongsheng
Abstract: The shape of eukaryotic cells is determined by the cytoskeleton associated with membrane proteins; however, the detailed mechanism of how the integral morphologies with structural stability is generated and maintained is still not fully understood. Here, based on the Frame‐Guided Assembly (FGA) strategy, we successfully prepared hetero‐liposomes with structural composition similar to that of eukaryotic cells by screening a series of transmembrane peptides as the leading hydrophobic groups (LHGs). It was demonstrated that the conformation and transmembrane mode of the LHGs played dominant roles during the FGA process. The FGA liposomes were formed with excellent stability, which may further provide evidence for the cytoskeleton–membrane protein–lipid bilayer model. Taking advantage of the biocompatibility and stability, the FGA liposomes were also applied to prepare novel drug delivery vehicles, which is promising in diagnostic imaging and cancer therapy applications. Abstract : Hetero‐liposomes with a structural composition similar to that of eukaryotic cells were prepared by constructing transmembrane peptide frames that mimicked the cell cytoskeleton structure. The conformation and transmembrane mode of the peptides played dominant roles during the frame‐guided assembly (FGA) process. FGA liposomes were formed with excellent stability and could be utilized as a drug delivery platform.